Characteristics of machining high hardness steels with face milling using carbide inserts and CBN - V.О. Zaloga (Технічна інженерія)
In modern mechanical engineering, face milling of high-hardness steels is a crucial process that enables high accuracy and surface quality of machined components. Carbide cutting inserts and cubic boron nitride (CBN) inserts are used as the main materials for cutting tool elements due to their high mechanical properties and ability to withstand significant loads. This article explores the characteristics of machining high-hardness steels using these tools, particularly their wear resistance and the impact of machining conditions on the wear of cutting plates. Carbide inserts have high hardness and resistance to thermal loads, making them suitable for machining high-hardness steels. However, the wear on such inserts can be significant if optimal machining conditions are not maintained. Cubic boron nitride (CBN) is known for its high hardness and wear resistance, making it an ideal material for machining hard steels. CBN plates provide a long tool life and high surface quality of machined parts. Research shows that the correct selection and optimization of machining parameters are the key to achieving the best results in face milling of high-hardness steels. Both carbide inserts and CBN have their unique advantages and challenges related to wear. Determining the optimal conditions for each type of cutting tool allows for minimizing wear and improving machining quality.